THE INSTRUMENTARY FOR IMPLEMENTING A PEDAGOGICAL MODEL FOR DEVELOPING DIGITAL COMMUNICATION COMPETENCE IN STUDENTS THROUGH THE USE OF CLOUD TECHNOLOGIES - POPOVICI, Ilona (Acta et Commentationes, Sciences of Education, 2021)
This article described the pedagogical model for the development of digital communication skills through the use of cloud technologies, as well as the pedagogical and technological tools for its implementation in a course.